United Kingdom legislation on pack sizes of analgesics: background, rationale, and effects on suicide and deliberate self-harm. - Hawton, K (2002)
Following increasing concern in the UK about the mortality and morbidity associated with self-poisoning with analgesics, especially paracetamol (Tylenol, acetaminophen), legislation was introduced in 1998 to modify packs sold over-the-counter. The most important change was a reduction in the maximum size of packs. In this paper the background to the legislation, the rationale behind it, and its early impact are reviewed. The changes have had significant positive initial benefits on the mortality and morbidity associated with self-poisoning with analgesics.